Influence of the COVID-19 pandemic on the concentration of aerosols observed over the Brazilian territory - Duarte, Renata Lopes; Santos, Marcela Granato Barbosa dos; França, Bruna Thomazinho (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
Due to the emergence of a new variant of viruses belonging to the family of coronaviruses, SARS-CoV-2, or COVID-19, still unknown to the scientific community and with great power of contagion and dissemination, several countries around the world have been forced to adopt measures of social restrictions, such as lockdown. As a result of the reduction in the circulation of people and transport, as well as in industrial activities, improvements in air quality were observed in several countries. Thus, with the objective of verifying the influence of the pandemic on the concentration of aerosols in the Brazilian atmosphere, this study carried out a bibliographic survey on the subject, and generated monthly maps of aerosol concentration in Brazil, in the years 2019 and 2020, for comparative purposes. As a result, it was observed that the restriction measures adopted had a positive effect on air quality, mainly in the South and Southeast regions of the country, where the largest population concentrations, vehicle fleets and industrial groups are located. In contrast, higher rates of aerosols were observed in the Brazilian Amazon, coinciding with the period of and occurrence of fires in this region related to slash-and-burn agriculture, which may explain the fact. Air pollution, as well as the accumulation of particles resulting from forest fires, aggravates the occurrence of respiratory problems, which can lead to more people being hospitalized, compromising the capacity of health systems.